2005
DOI: 10.2106/jbjs.c.01533
|View full text |Cite
|
Sign up to set email alerts
|

The Spinoglenoid Ligament

Abstract: This study revealed the presence of the spinoglenoid ligament in all of the shoulders that were examined, with some variation in the size of the ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…18,110 The spinoglenoid ligament has been reported to be present in 3% to 100% of cadavers. 32,[36][37][38]60,82 However, a 2005 study by Plancher et al 82 demonstrated the ligament's presence in all 58 study cadavers. This study proposed that the differences in the presence of the spinoglenoid ligament between studies were due to specimen preparation.…”
Section: Anatomymentioning
confidence: 95%
See 2 more Smart Citations
“…18,110 The spinoglenoid ligament has been reported to be present in 3% to 100% of cadavers. 32,[36][37][38]60,82 However, a 2005 study by Plancher et al 82 demonstrated the ligament's presence in all 58 study cadavers. This study proposed that the differences in the presence of the spinoglenoid ligament between studies were due to specimen preparation.…”
Section: Anatomymentioning
confidence: 95%
“…More important, it also showed that the spinoglenoid ligament lies an average of 4.6 mm above the suprascapular nerve and becomes taut in positions of adduction and internal rotation (the follow-through phase in throwing) because of its ligamentous insertion into the posterior capsule. 81,82 This variation can be significant in causing pathology of the nerve.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…The first type, labelled as a thin band, was previously observed by Cummins et al [77] and Demaio et al [78]. Accordingly, Plancher et al [79] described irregular and quadrangular types of ligament. The triangular ITSL was originally proposed by Won et al [76].…”
Section: Morphological Factors Predisposing To Snesmentioning
confidence: 84%
“…According to a cadaveric study by Plancher et al [21] the spinoglenoid ligament was present in all 58 specimens lying 4.8mm over the suprascapular nerve. Another study by the same author proposed that the nerve is being taught in positions of adduction and internal rotation [22].…”
Section: Anatomymentioning
confidence: 99%